A war of words in the discourse of trade : the rhetorical constitution of metaphor - Eubanks, Philip, 1954- (Southern Illinois University Press, 2000)
"A War of Words in the Discourse of Trade: The Rhetorical Constitution of Metaphor by Philip Eubanks challenges traditional accounts of metaphor and significantly expands theories of "conceptual" metaphor by examining Trade Is War as it occurs in concrete discourse." "Although scholarly interest in metaphor as an aesthetic, linguistic, and cognitive phenomenon has long endured, Eubanks is among the first to consider metaphor in its sociohistorical role. Questioning major accounts of metaphor from Aristotle to the present, Eubanks argues that metaphor is not just influenced by but actually is constituted by its concrete operation."